Involvement of the Host Cell Nuclear Envelope Membranes in the Replication of Japanese Encephalitis Virus - Zebovitz, E. (Infect Immun, 1974)
The distribution of viral ribonucleic acid (RNA) on various cell membrane fractions derived from a porcine kidney cell line infected with Japanese encephalitis virus was investigated. At 40 h postinfection, after virus growth had reached its peak, three viral RNAs, 45S, 27S, and 20S, were associated with the cytoplasmic membranes and intact nuclei. The amount of each RNA associated with the nucleus was two- to fivefold greater than that present with the cytoplasmic membranes. Treatment of washed infected nuclei with 1.0% Triton X-100, which removed the outer nuclear envelope membrane, also removed the viral RNA. When the nucleus was fractionated into nuclear envelope membranes and a large particle fraction which sedimented at 600 × g, nearly all of the viral RNA remained associated with the envelope membranes. The nuclear envelope membranes contained higher viral RNA polymerase activity than the cytoplasmic membranes derived from the same cells. These data suggest that major sites for Japanese encephalitis virus RNA synthesis may be localized on or in very close association with the nuclear envelope membranes.